2021
DOI: 10.1021/acs.energyfuels.1c00808
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Role of Oxygen in CO and Propylene Oxidation over a Pt–Pd-Based Wiremesh Catalyst as a Retrofit Emission Control Device for Four-Stroke Gasoline Spark-Ignited Motorcycles

Abstract: Over 200 million motorcycles in use worldwide account for a substantial portion of global mobile source total hydrocarbons (THC) and carbon monoxide (CO) emissions. In Tehran, capital of Iran, ultrarich inefficient combustion in gasolinefueled motorcycles results in significantly high CO and THC emissions. Motorcycle catalysts can reduce CO and C 3 H 6 (as a representative hydrocarbon) emission factors by 60−80%. In the present work, CO and propylene oxidation over a commercial Pt− Pd-based wiremesh catalyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The oxidation of gaseous hydrocarbons on solid catalysts is common in many engineering applications, including after-treatment systems in engines, fuel reforming, power generation, and chemical processing. Since the early discovery of the catalytic behavior of platinum (Pt) Davy, extensive research on the oxidation of hydrocarbons on catalysts such as palladium (Pd), rhodium (Rh), and Pt has been conducted, and the use of such catalysts in the applications mentioned above has gained considerable interest. However, many of the underlying processes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of gaseous hydrocarbons on solid catalysts is common in many engineering applications, including after-treatment systems in engines, fuel reforming, power generation, and chemical processing. Since the early discovery of the catalytic behavior of platinum (Pt) Davy, extensive research on the oxidation of hydrocarbons on catalysts such as palladium (Pd), rhodium (Rh), and Pt has been conducted, and the use of such catalysts in the applications mentioned above has gained considerable interest. However, many of the underlying processes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ambient-temperature catalytic CO oxidation is an important process for the control of indoor air quality and cold-start emission in automobiles with catalytic converters. Various studies have extensively investigated catalytic CO oxidation in recent decades for industrial applications. However, at low temperatures (<200 °C), automotive catalysts are poisoned by emissions and, therefore, exhibit limited activity. Consequently, supported noble metal (mainly Pt and Au)-based catalysts have been extensively studied because of their high CO oxidation activity and stability at low reaction temperatures. , Previous studies on Pt-based catalysts have revealed the mechanism of low-temperature CO oxidation by O 2 , showing that the adsorption of CO on Pt favors oxidation. However, too strongly adsorbed CO on metallic Pt also acted as poisoning (i.e., inactive) sites at lower temperatures. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Transition metals, such as platinum (Pt), are widely known for their catalytic performance in both oxidizing and reducing reactions and have been widely applied industrially for hydrocarbon oxidation, 1 for abatement of automobile exhaust gases, 2,3 in fuel cells 4 and in catalytic reforming. 5 The use of metallic nanoparticles as catalysts is motivated not only by their large active surface area but also by their special catalytic properties due to their particular size, shape and structure.…”
Section: Introductionmentioning
confidence: 99%